Effects of intravenous laser irradiation on viral load and T lymphocytes in people living with HIV/AIDS - Ramos, Fabiana Tomé; Lobo, Maria Cecília Yoshioka; Miot, Helio Amante; Minicucci, Eliana Maria; Alencar, Rubia de Aguiar (FapUNIFESP (SciELO), 2025)
OBJECTIVE: To evaluate the effectiveness of intravenous laser irradiation of blood in reducing viral load and increasing LT-CD4+ and LT-CD8+ in people living with HIV/AIDS. METHOD: Randomized, controlled, parallel, single-blind clinical trial. Twenty-eight participants were allocated to the intervention (ILIB n = 15) and control (CTRL n = 13) groups. The ILIB group received irradiation with red laser (660 nm), applied to the radial artery (30 minutes/day for 20 days), with a total energy of 180 J. The CTRL group received a sham intervention (without light emission). Viral load and LT-CD4+ and LT-CD8+ counts were assessed at the end. RESULTS: Both groups showed a reduction in viral load (ILIB: -1.7 log; CTRL: -2.3 log). In the ILIB group, 61.5% of participants achieved an undetectable viral load (p = 0.449). There was no increase in CD4+ LT count (p = 0.287), but a non-significant reduction in CD8+ LT count was observed in the ILIB group (p = 0.173). There were no statistically significant differences between groups for any outcome (p > 0.17). The study was stopped prematurely during the interim analysis. CONCLUSION: ILIB, as an adjuvant therapy to ART, did not show clinical or statistical superiority in the immunological and virological parameters evaluated. BRAZILIAN REGISTRY OF CLINICAL TRIALS (REBEC): RBR-7j9rv5d (https://ensaiosclinicos.gov.br/trial/10848).